2005
DOI: 10.1080/08035250410020235
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of an asthma clinical pathway for children in general practice

Abstract: Admissions to hospital for asthma decreased, as did attendance at the Children's Emergency Department. Prescriptions for asthma medication changed in the direction anticipated with compliance with the asthma clinical pathway. However, we found no evidence within the study that implementation of the asthma clinical pathway by general practitioners resulted in lower morbidity than those general practitioners who did not implement the pathway. Possible explanations are that these general practitioners were alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…94 95 supplemental feedback protocols, 5 and structured pathways/algorithms. 37,96 Several studies included children. 5,37,46,85,96 Nine studies reported a reduction in ED visits or hospitalizations 5,[36][37][38]46,84,85,95,96 (5%-60%) among pre-post studies (all statistically significant) and 1% to 7% among the RCTs.…”
Section: Clinical Pharmacy Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…94 95 supplemental feedback protocols, 5 and structured pathways/algorithms. 37,96 Several studies included children. 5,37,46,85,96 Nine studies reported a reduction in ED visits or hospitalizations 5,[36][37][38]46,84,85,95,96 (5%-60%) among pre-post studies (all statistically significant) and 1% to 7% among the RCTs.…”
Section: Clinical Pharmacy Supportmentioning
confidence: 99%
“…Fifteen studies were identified that included the provision of asthma guidelines in a more accessible format (eg, "pocket" versions), [36][37][38] use of a specific algorithm, pathway, or flow sheet, 37 …”
Section: Decision Supportmentioning
confidence: 99%
“…A number of studies reported substantial improvement in quality both in inpatient [1,11,14,18,21,32,50,53,57,60,62,68,78] and outpatient settings [13,29,37,40,42,46]. Numerous studies, including six RCTs [4,7,38,51,63,71], failed to show any positive effects on quality associated with practice guidelines [5,10,20,25,26,36]. Results were mixed in 12 studies, in which practice guidelines improved quality for certain outcomes or patient subgroups but not others [8,23,24,41,43,52,54,55,58,59,73,74].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%
“…21 Mitchell et al used education sessions to outline validated clinical pathways, with a subsequent decrease in oral reliever medications (48.4% in intervention group, 28.6% in control, p<0.001), and reduction in hospitalisation. 17 In the only study to find no impact on prescribing practice, Witt et al found that guideline based education delivered personally or via correspondence did not change prescribing rates of SABAs or ICS. 14 Some of the studies examined more multifaceted interventions.…”
Section: Impact Of Strategies To Improve Prescribingmentioning
confidence: 99%
“…Peer leader group: 6.5 fewer asthma symptom days (non -significant reduction) 17 Increase in use of ICS in group C (0.4 puffs/day compared to 0.3 puffs/day for groups A and B, p<0.05) (positive change)…”
mentioning
confidence: 99%